Effects of Use of Metformin or Combination of Metformin and Pioglitazone on Oxidative Stress in Type 2 Diabetes Mellitus - Temiz Gençoğlu, Ayşe Tuğçenur; Asfuroglu Kalkan, Emra; Zengin, Oğuzhan; Erel, Özcan; Ateş, İhsan (Journal of Medical Biochemistry, 2025)
Aim: We aimed to examine how oxidative stress changes after treatment and its relationship with metabolic parameters in patients diagnosed with Type 2 Diabetes Mellitus and given metformin or metformin-pioglitazone combination. Methods: The study population consisted of a total of 60 patients, including the group diagnosed with Type 2 Diabetes Mellitus (T2DM) and given metformin 2x1000 mg (n=30) and the group given metformin-pioglitazone 2x15/1000 mg combination (n=30). Serum IMA (ischemia modified albumin), TAS (total antioxidant status), TOS (total oxidant status) and thiol - disulphide homeostasis were measured before and after 12 weeks of treatment. Results: No significant change was detected in Native SH and Total SH levels in both Metformin and combination groups. IMA level increased significantly in both drug groups (p=0.03, p=0.01, respectively). Although the TAS level increased in both groups, no significant change was detected. While TOS and OSI index decreased significantly in the combination group (p<0.001), the decrease was not significant in the metformin group. No significant difference was detected between Native SH, Total SH, Disulfide, IMA, TAS, TOS levels and OSI index changes of both drug groups. Conclusion: We found that the anti-diabetic drugs used did not have a significant effect on oxidative stress.